Activity of Compound Agrimony Enteritis Capsules against invasive candidiasis: Exploring the differences between traditional Chinese medicine prescriptions and its main components in the treatment of diseases. (15th September 2021) - Li, Jun; Jin, Ze-Hua; Li, Jia-Sheng; Su, Liu-Yan; Wang, Ying-Xian; Zhang, Yi; Qin, Ding-Mei; Rao, Gao-Xiong; Wang, Rui-Rui
Abstract: Ethnopharmacological relevance: Compound Agrimony Enteritis Capsules (FFXHC) is an ethnomedicine derived from Yi Nationality Herbal Medicine for the treatment of enteritis. We found that compared to berberine hydrochloride (BBR), a component of this medicine, FFXHC was more efficacious in the mouse model of IC mice in significantly alleviating lung and intestinal lesions. " Our study provides a novel perspective into the pharmacological mechanism of action of the ethnic compound FFXHC. Aim of the study: To determine the underlying mechanism of the superiority of FFXHC over BBR in IC. Materials and methods: The susceptibility of Candida albicans to FFXHC was evaluated in vitro . The mouse model of IC was established and the survival rate, weight change, the number of organ colonies, and immune organ coefficient of the mice were determined, the effect of FFXHC on the immune function of mice, including changes in the number of immune cells, levels of the related inflammatory cytokines (INF-γ, TNF-α, MCP-1, IL-6, and IL-17A), and the antimicrobial peptide, LL-37 (CRAMP in mice), were determined. Mice feces were collected and changes in the intestinal microecology were studied. Results: Our findings indicated that FFXHC was not active against Candida albicans and did not restore the sensitivity of the resistant strain in vitro ; however, it had a therapeutic effect that improve survival rate on mice with IC. The number of lymphocytes and neutrophils of mice with IC treated with FFXHC increased significantly. The intestinal microecology of mice was restored and the abundance of the probiotic Bacteroides was increased, which further stimulated the production of the antimicrobial peptide, LL-37, which is required for acquired immunity. Furthermore, the levels of Th cell-related cytokines, including INF-γ, TNF-α, and IL-17A were significantly increased, whereas those of the proinflammatory cytokines, IL-6 and MCP-1, decreased. With the activation of acquired immunity, the immune function of mice was restored, the body weight and survival rate of mice improved considerably, the coefficients of the thymus and spleen increased, and the number of fungal colonies in the lung and kidney decreased. Conclusions: FFXHC could eliminate fungi by increasing the relative abundance of probiotics in Bacteroides and the number of neutrophils, thereby promoting the production of CRAMP and resulting in a fungicidal effect, leading to acquired immunity. Although BBR has an antifungal effect, we found that it was not as effective as FFXHC. Graphical abstract: Image 1